THE ROLE OF COST OF LOAN IN BANKING LOAN DYNAMICS: BIFURCATION AND CHAOS ANALYSIS - Moch. Fandi Ansori; Siti Khabibah (Barekeng)
The gradient adjustment process is used to create a dynamic model of banking loan. The sign of the loan’s marginal profit determines how much money will be loaned in the future. In this research, using bifurcation theory, we investigate the cost of loan in the dynamics of a bank’s loan. The results of the analysis indicate that the stability of the loan equilibrium might be impacted by the cost of loan. Loan equilibrium may become unstable through transcritical bifurcation if the cost of the loan is sufficiently high. The loan equilibrium may become unstable through flip bifurcation and path to chaos, however, if the cost of loan is too low. If the cost of loan lies between the bifurcation values, the loan equilibrium is stable. The numerical simulations back up these conclusions. Additionally, we display the Lyapunov exponent graph, which shows the presence of chaos, and the chaotic loan graph, which is sensitive to the initial condition.